Retratos da leitura no Brasil: entre velhas e novas barreiras - OLIVEIRA, Elizabete Joely Silva de (2021)
The main concern of the study is the deficit in the issue of encouraging reading, its democratization and importance for the development of society. Thus, it focuses on the library environment as a democratic and cultural space. It seeks to show the reading situation in the country through the Retratos da Leitura research in Brazil. As a methodology, bibliographical and documentary research is used, the latter supported by the bulletins of Instituto Pró-livro - IPL published in 2008, 2011 and 2016, in order to analyze the data in a qualitative-quantitative perspective. The study provides an overview of the reading situation in Brazil, pointing to old and new barriers related to reading, as well as the profile of readers and their difficulties.